Toward global mapping of methane with TROPOMI: first results and intersatellite comparison to GOSAT - Hu, Haili; Butz, André (Geophysical research letters, 2018)
The TROPOspheric Monitoring Instrument (TROPOMI), launched on 13 October 2017, aboard the Sentinel-5 Precursor satellite, measures reflected sunlight in the ultraviolet, visible, near-infrared, and shortwave infrared spectral range. It enables daily global mapping of key atmospheric species for monitoring air quality and climate. We present the first methane observations from November and December 2017, using TROPOMI radiance measurements in the shortwave infrared band around 2.3 μm. We compare our results with the methane product obtained from the Greenhouse gases Observing SATellite (GOSAT). Although different spectral ranges and retrieval methods are used, we find excellent agreement between the methane products acquired from the two satellites with a mean difference of 13.6 ppb, standard deviation of 19.6 ppb, and Pearson's correlation coefficient of 0.95. Our preliminary results capture the latitudinal gradient and show expected regional enhancements, for example, in the African Sudd wetlands, with much more detail than has been observed before.
Gesehen am 03.12.2018